Hydrogen-rich water treatment increased several phytohormones and prolonged the shelf life in postharvest okras - Dong, Wanqi; Cao, Shifeng; Zhou, Qihang; Jin, Shuwan; Zhou, Chujiang; Liu, Qingli; Li, Xu; Chen, Wei; Yang, Zhenfeng; Shi, Liyu (Frontiers in Plant Science, 2023)
The effects of hydrogen-rich water (HRW) treatment on the contents of several phytohormones and shelf life of postharvest okras were studied. The results showed that HRW treatment delayed okra senescence and maintained fruit quality during storage. The treatment upregulated all of the melatonin biosynthetic genes such as AeTDC, AeSNAT, AeCOMT and AeT5H, contributing to the higher melatonin content in the treated okras. Meanwhile, increased transcripts of anabolic genes but lower expression of catabolic genes involved in indoleacetic acid (IAA) and gibberellin (GA) metabolism were observed in okras when treated with HRW, which was related to the enhanced levels of IAA and GA. However, the treated okras experienced lower abscisic acid (ABA) content as compared to the non-treated fruit due to the down-regulation of its biosynthetic genes and up-regulation of the degradative gene AeCYP707A. Additionally, there was no difference in γ-aminobutyric acid between the non-treated and HRW-treated okras. Collectively, our results indicated that HRW treatment increased levels of melatonin, GA and IAA, but decreased ABA content, which ultimately delayed fruit senescence and prolonged shelf life in postharvest okras.